Facile synthesis of zwitterionic polyglycerol dendrimers with a β-cyclodextrin core as MRI contrast agent carriers. Issue 41 (5th October 2016) - Han, Yuxin; Qian, Yue; Zhou, Xiaoxuan; Hu, Hongjie; Liu, Xiangrui; Zhou, Zhuxian; Tang, Jianbin; Shen, Youqing
Abstract : A facile synthesis method of a zwitterionic polyglycerol dendrimer was developed, providing an ideal carrier for drug and imaging probe delivery. Abstract : Dendrimers with uniform hyperbranched structures are ideal carriers for drug and imaging probe delivery; however, the complicated synthesis and poor biocompatibility of these molecules hinder their biological applications. In this study, a facile method for the synthesis of a biocompatible polyglycerol dendrimer (PGD) was developed by reducing the synthesis steps and simplifying purification with β-cyclodextrin (β-CD) as the core, and a zwitterionic surface of the dendrimer was achieved by modifying withl -cysteine. The synthesized zwitterionic PGD could avoid liver capture by the mononuclear phagocyte system because of its anti-fouling property. PGD was used to develop an extracellular dendritic MRI contrast agent (CA), which showed higher and longer MRI contrast enhancement in blood pools than the clinically used contrast agent (Magnevist) with minimal retention in organs, especially the liver. Hence, the zwitterionic PGD with excellent anti-fouling property and facile synthesis could be a promising carrier for drug and imaging probe delivery.